Repetitive DNA in the Architecture, Repatterning, and Diversification of the Genome of Aegilops speltoides Tausch (Poaceae, Triticeae) - Pollak, Yulia; Zelinger, Einat; Raskina, Olga (Frontiers in Plant Science, 2018)
The genome’s adaptability to environmental changes, especially during rapid climatic fluctuations, underlies the existence and evolution of species. In the wild, genetic and epigenetic genomic changes are accompanied by significant alterations in the complex nuclear repetitive DNA fraction. Current intraspecific polymorphism of repetitive DNA is closely related to ongoing chromosomal rearrangements, which typically result from erroneous DNA repair and recombination. In this study, we addressed tandem repeat patterns and interaction/reshuffling both in pollen mother cell (PMC) development and somatogenesis in the wild diploid cereal Aegilops speltoides, with a focus on genome repatterning and stabilization. Individual contrasting genotypes were investigated using the fluorescent in situ hybridization (FISH) approach by applying correlative fluorescence and electron microscopy. Species-specific Spelt1 and tribe-specific Spelt52 tandem repeats were used as the markers for monitoring somatic and meiotic chromosomal interactions and dynamics in somatic interphase nuclei. We found that, the number of tandem repeat clusters in nuclei is usually lower than the number on chromosomes due to the associations of clusters of the same type in common blocks. In addition, tightly associated Spelt1–Spelt52 clusters were revealed in different genotypes. The frequencies of nonhomologous/ectopic associations between tandem repeat clusters were revealed in a genotype-/population-specific manner. An increase in the number of tandem repeat clusters in the genome causes an increase in the frequencies of their associations. The distal/terminal regions of homologous chromosomes are separated in nuclear space, and nonhomologous chromosomes are often involved in somatic recombination as seen by frequently formed interchromosomal chromatin bridges. In both microgametogenesis and somatogenesis, inter- and intrachromosomal associations are likely to lead to DNA breaks during chromosome disjunction in the anaphase stage. Uncondensed/improperly packed DNA fibers, mainly in heterochromatic regions, were revealed in both the meiotic and somatic prophases that might be a result of broken associations. Altogether, the data obtained showed that intraorganismal dynamics of repetitive DNA under the conditions of natural out-crossing and artificial intraspecific hybridization mirrors the structural plasticity of the Ae. speltoides genome, which is interlinked with genetic diversity through the species distribution area in contrasting ecogeographical environments in and around the Fertile Crescent.